Sistem Otomatisasi Pemberi Pakan Pada Peternakan Bebek Dengan Arduino UNO dan Bluetooth Menggunakan SmartPhone - Yusra Fernando; Ramadhan Lukman; Akhmad Jayadi; Rini Nuraini (TIN: Terapan Informatika Nusantara, 2022)
In the Ayem Bareng Duck Livestock Group, the process of feeding currently used is still manual, namely by placing feed in the feed storage container provided in the duck cage. This becomes an obstacle for farmers because the feeding time is done 2-3 times a day, because it will take time and cost to get to the location of the duck coop. With the obstacles experienced, the author proposes to make a Prototype of a tool that can feed ducks automatically, on a scheduled basis and the amount of feed given can also be regulated. The components used in the tool are Arduino UNO, DC motor, Bluetooth Module HC-06 and others. The delivery method used is Prototype Evolutioner. The result of this research is a Prototype tool that can feed ducks automatically. With a feeding process that runs automatically and on a scheduled basis, the feeding will be regular, timely and the amount of feed given will also be precise and consistent. The process of setting the schedule and number of feeds can be done using an Android smartphone that is connected to the device via a Bluetooth connection. Another benefit of automatic feeding is that the time and costs incurred by farmers for feeding livestock will be less. The results of the research are tools that are able to feed automatically and on a scheduled basis.